Low-molecular-weight organic acids enable biochar to immobilize nitrate. (February 2020) - Heaney, Natalie; Ukpong, Emem; Lin, Chuxia
Abstract: Batch experiments were conducted using two biochar materials produced from different feedstocks to examine the behavior of solution-borne nitrate in the presence and absence of three model low-molecular weight organic acids (LMWOAs). The results showed that the biochar materials alone were not able to remove the solution-borne nitrate. LMWOAs caused protonation of the biochar surfaces and consequently enabled the biochar materials to adsorb nitrate from the solution. Different types of LMWOA had different capacities to immobilize solution-borne nitrate. Over 80% of the solution-borne nitrate could be removed within 72 h in the presence of citric acid or malic acid. By comparison, removal rate of nitrate was lower in the presence of oxalic acid, possibly due to competition of oxalate ion with nitrate for the available adsorption sites on the biochar surfaces. Nitrate adsorption onto the MSP700 biochar in the presence of all three-LMWOAs followed first order and second order kinetics, suggesting that the immobilization of nitrate involved complex interplay of physisorption and chemisorption. Nitrate adsorption onto RH700 biochar in citric and malic acid treatment systems followed second order kinetics. In the presence of oxalic acid for both biochar materials, nitrate adsorption showed perfect correlation R 2  = 1 for both models. Highlights: The biochar materials alone were not able to remove the solution-borne nitrate. Low-molecular-weight organic acids (LMWOAs) protonated the biochar surfaces. This enabled biochar to adsorb nitrate from the solution. Different types of LMWOA affected nitrate immobilization differently. LMWOA-driven nitrate adsorption followed first or/and second order kinetics.